2018
DOI: 10.14444/5036
|View full text |Cite
|
Sign up to set email alerts
|

Review of Vertebral Augmentation: An Updated Meta-analysis of the Effectiveness

Abstract: Background: To update vertebral augmentation literature by comparing outcomes between vertebroplasty (VP), balloon kyphoplasty (BKP), vertebral augmentation with implant (VAI), and nonsurgical management (NSM) for treating vertebral compression fractures (VCFs).Methods: A PubMed literature search was conducted with keywords kyphoplasty, vertebroplasty, vertebral body stent, and vertebral augmentation AND implant for English-language articles from February 1, 2011, to November 22, 2016. Among the results, 25 me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 57 publications
(39 reference statements)
0
33
0
Order By: Relevance
“…[3] Here we provide a short perspective reviewing the pros and cons for these 3 treatment options for managing traumatic/atraumatic OVCFs. [1][2][3][4][5][6][7][8][9][10][11][12][13]…”
Section: Introductionmentioning
confidence: 99%
“…[3] Here we provide a short perspective reviewing the pros and cons for these 3 treatment options for managing traumatic/atraumatic OVCFs. [1][2][3][4][5][6][7][8][9][10][11][12][13]…”
Section: Introductionmentioning
confidence: 99%
“…More recently, several vertebral implants including stents, jacks, cages, and fracture reduction systems, have been used for VA [12]. However, there is no Level I evidence to suggest that these implants improved outcomes compared to traditional VA in terms of pain or disability score reduction [13].…”
Section: Vertebral Augmentationmentioning
confidence: 99%
“…Indeed, the first use of acrylic-based cement (PMMA) in the spine was performed by Galibert et al 18 in 1987 as a way to stabilize a vertebral hemangioma. Since then, more than 52 level 1 and level 2 studies were published 9,19 with the overwhelming majority in favor of the use of vertebral augmentation; some of those studies are shown in Table 2. It is now difficult to argue against the effectiveness of these minimally invasive interventions.…”
Section: Coverage Rationale For Vertebral Augmentationmentioning
confidence: 99%
“…Balloon kyphoplasty also tended to have better vertebral body height restoration than vertebroplasty. 19 The 2013 Kyphoplasty and Vertebroplasty National Institute for Health and Care Excellence Technology Appraisal Guidance…”
Section: Systematic Reviews and Meta-analysesmentioning
confidence: 99%